Factors affecting utilization of ANC service among the mothers having children under 2 years of Panauti municipality of Kavre district in year 2014. (2014)
ABSTRACT: A descriptive cross-sectional study was carried out with the main objective of assess the factors affecting utilization of ANC service among the mothers having children under 2 years of Panauti municipality of Kavre District. The sampling method was systematic random sampling. The data were analyzed using univariate frequency table and chisquare for bivariate analysis. . This was completely a non-experimental cross-sectional study and the sampling method was systematic random sampling. The study revealed that 58% of respondents belonged to (16-26) years of age and 9.9% belonged to 34-40 years. Similarly, 72.3% were literate, 62.4% were Brahmin and Chhetri, and 86.1% respondents belonged to high economic status. And most (44.6%) of the respondents were housewife. Among total respondents, more than two third were users of ANC services. The factors age, economic status, ethnicity, availability of ANC service provider, accessibility of ANC health services, TV, radio, family support, friends etc. did not show the association to the utilization of ANC service The bivariate analysis revealed relationship only between education status and media exposure (board/poster/pamphlet/books). Chi-square test was applied to show the association between dependent variable and independent variables.